International Events Activity as the Viewpoint of Influence on the Economic and Legal Aspects of the Tourist Infrastructure - S.V. Petrova; V.A. Fomenko (Universitas Muhammadiyah Sidoarjo, 2020)
Tourism is one of the most stable and dynamically developing sectors of the global economy. Despite the economic turmoil of recent years, the number of tourist arrivals is constantly growing. In this flow, the percentage of tourists who prefer to visit various cultural, sports, business, political and other events of various scales also increases annually. People’s desires to attend an event or at some event gradually formed an entire industry, which, in turn, began to manage these desires, bringing considerable benefits to the organizers of the events and destinations - the owners of these events in the form of taxes, activation of infrastructure and population. Sochi city, due to its unique geo-economic and geopolitical location, rich history and rapidly accumulating tourist experience, is becoming one of the most attractive Russian destinations in the field of event tourism. The main problem associated with the development of international event tourism as a basis for influencing tourism infrastructure is the lack of methodological materials for the integrated development of this type of tourism, taking into account modern requirements, the insufficient involvement of marketing technologies to create and promote this tourism product in the domestic and foreign markets and, as a result, in its insufficient socio-economic efficiency. Event tourism can be considered not only as a type of tourism, but also as a strategy for the development of the economic and legal sphere of tourist infrastructure.